Relationship Between Big Five Personality Dimensions, Chronotype, and DSM-V Personality Disorders - Staller, Naomi; Randler, Christoph (Frontiers in Network Physiology, 2021)
Morningness-eveningness (M/E) is an important variable in individual differences and has an impact on many areas of life including health in general and mental health. In previous work eveningness has shown to correlate to personality disorders (PDs) and mental instability such as psychoticism, depression, and bipolar disorders. Therefore, a relationship between M/E and PDs can be assumed but has never been tested. The aim of this study was to assess a possible relationship between DSM-5-PDs and circadian timing (chronotype; M/E). We used the Morningness-Eveningness Stability Scale improved and clock time-based measurements, the PID-5 brief version and the Big Five brief version. Sample: N=630; mean age: 27.76 years, SD: 11.36 years; 137 male, 489 female, 4 diverse. In this short screening a relationship between eveningness and DSM-5-personality traits, (evening-oriented participants showing a higher PID-5 score: morningness -.208/ p<.001; eveningness: .153/ p<.001) was found. Moreover, participants with high levels of distinctness (energy fluctuations during the day) are prone to PDs too, with distinctness being the best predictor for a high PID-5 score in this sample (.299 / p<.001).